A experiência do trabalho de campo no universo da comunicação - Travancas, Isabel Siqueira (Universidade de São Paulo | Escola de Comunicações e Artes, 2014)
The purpose of this communication is to discuss the experience of fieldwork based upon two different research projects: one with journalists and another withother university students. The objective is to discuss the particulars of anthropological research and its qualitative methods, which included participant observation, open and in-depth interviews and the maintenance of a field diaries. I will also analyze the difficulty of combining this research with quantitative methods that bring new perspectives to the field but are often perceived as "lesser" tools. Each of the two projects related here had its distinct problems, but the analysis of these research experiences within the field of communications allows for further discussions regarding the use of different research methods and the evaluation of the contributions of anthropological methodology.